2007
DOI: 10.1016/j.ijgo.2007.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Polygamy and the use of contraceptives

Abstract: Polygamy influences contraceptive use and the role of co-wives in this regard merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Women in polygamous marriages are found to use modern methods less than those in monogamous marriages. 11 According to all Demographic and Health Surveys (DHSs) of 22 Sub-Saharan African countries conducted in 2000, the percentage of married women aged 15-49 years with husbands with more than one wife varies from 11.4% in Zimbabwe to 26.5% in Côte d'Ivoire and 53% in Guinea.…”
Section: Modeling Contraceptive Usementioning
confidence: 99%
“…Women in polygamous marriages are found to use modern methods less than those in monogamous marriages. 11 According to all Demographic and Health Surveys (DHSs) of 22 Sub-Saharan African countries conducted in 2000, the percentage of married women aged 15-49 years with husbands with more than one wife varies from 11.4% in Zimbabwe to 26.5% in Côte d'Ivoire and 53% in Guinea.…”
Section: Modeling Contraceptive Usementioning
confidence: 99%
“…There is a body of literature that suggests some socio economic and demographic factors, such as residence [ 14 ], education [ 15 , 16 ], age [ 16 ], economic status [ 17 ], employment status [ 18 ], religion [ 19 , 20 ], parity [ 21 ], access to media [ 15 , 19 ], autonomy [ 22 , 23 ], desire for children [ 23 ], marital status [ 14 ] and partner communication [ 19 ], have been associated with the use ofMC. In addition, other studies revealed that women’s power and autonomy is favorably related to better reproductive health and use of contraceptives [ 24 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Against that background, contraceptive use is often believed to be contrary to the teachings of Islam Duze and Mohammed 2006). Moreover, polygyny, which is permitted by Islam, encourages higher fertility rates and lower contraceptive use (Baschieri et al 2013;Audu et al 2008). Furthermore, the value system of purdah, which restricts women's autonomy and movement out of the family home, impedes their access to family planning and other reproductive health services (Konje and Ladipo 1999).…”
Section: Introductionmentioning
confidence: 99%